Effects of dietary Lactobacillus acidophilus and Bacillus subtilis on laying performance, egg quality, blood biochemistry and immune response of organic laying hens. Issue 5 (28th November 2015) - Forte, C.; Moscati, L.; Acuti, G.; Mugnai, C.; Franciosini, M. P.; Costarelli, S.; Cobellis, G.; Trabalza‐Marinucci, M.
Summary: The objective of this study was to evaluate the effects of two different probiotic micro‐organisms on the performance, egg quality and blood parameters of organically reared hens. A total of 900 16‐week‐old Hy‐Line layer hybrids were randomly assigned to three groups of 300 birds each. The control (CTR) group was fed a corn–soya bean cake‐based diet; the L group was fed the same diet supplemented with 0.1% Lactobacillus acidophilus, while the B group was fed the same diet supplemented with 0.05% Bacillus subtilis . Data were recorded at the beginning (weeks 5 and 6: T1) and at the end (weeks 19 and 20: T2) of the experiment, and no differences in hen performance were recorded between dietary groups or sampling times. All of the investigated clinical chemistry parameters, except GGT, were affected by diet (p < 0.05), with the best results recorded for the probiotic‐treated groups. The immune‐response values showed higher blood bactericidal activity in the B and L groups at T2 (p < 0.05) and a lower lysozime concentration in the B group at T1. Higher antibody production against Newcastle disease virus was observed in the L group compared to the CTR (p = 0.013). No differences in oxidative status were recorded, and no effects of diet on egg quality were observed. Among the physical egg characteristics, only the Roche scale colour was affected by diet (p < 0.05): the egg yolk was paler in the L group. The age of the hen was the most relevant factor affecting physical egg characteristics. The chemical parameters of the egg were almost unaffected by supplementation with probiotics except for the lipid content, which decreased with the L diet (p < 0.05). Both probiotic inclusions had beneficial effects on hen metabolism and welfare, and L. acidophilus induced the best immune response.